Light absorption by inhomogeneous semiconductor film - Baraban, L.; Lozovski, V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
Processes of light absorption by thin semiconductor film in the framework of local-field method are studied. The film is inhomogeneously implanted with O⁺ ions. A distribution of implanted layer is characterized by different profiles. The effective susceptibility (response to the external field) and dissipative function of inhomogeneous in thickness semiconductor film were calculated. The absorption spectra are numerically calculated as a function of the frequency and angle of incidence. It was obtain that light absorption spectra are strongly dependent on profile distributions of implanted impurities along the film thickness.